9. FACTORS BEHIND THE ACHIEVEMENTS OF THE TRANSMIGRATION PROGRAM FAKTOR-FAKTOR DIBELAKANG PENCAPAIAN PROGRAM TRANSMIGRASI - Aleh Human Saleh (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2018)
ABSTRACT This study was part of dissertation entitled ‘Analysis of The Indonesian Transmigration Model and Some Policy Implications for Extension’. This study was heavily based on a review of existing literature and research related to the transmigration program. The Transmigration program was viewed as a combination of push factors that pressure migrants to seek better opportunities and pull factors that attract migrants to a particular location. There are three major components behind the achievements of the transmigration program, namely: government efforts as facilitating factors, potential migrants as push factors to leave the place of origin, economics and non economics factors as pull factors to come to the destination area. ABSTRAK Penelitian ini merupakan bagian dari disertasi yang berjudul ‘Analisis Model Transmigrasi Indonesia dan Beberapa Implikasi Kebijakan Terhadap Penyuluhan’. Penelitian ini didasarkan pada review literatur yang ada serta hasil penelitian yang terkait dengan program transmigrasi. Program transmigrasi dipandang sebagai sebuah kombinasi dari faktor-faktor pendorong yang menekan migran untuk mencari kesempatan yang lebih baik dan faktor-faktor penarik yang memberikan daya tarik bagi migran ke suatu lokasi tertentu. Ada tiga komponen utama dibelakang pencapaian program transmigrasi yakni: usaha pemerintah sebagai faktor fasilitas, potensi migran sebagai faktor pendorong untuk meninggalkan daerah asal, faktor ekonomi dan non-ekonomi sebagai faktor penarik bagi migran untuk datang ke daerah yang dituju.